Offline digital – digital offline: The potential of offline digitised information for the production, distribution and appropriation of human knowledge - Schiefer, U.; Carvalho, A. L.; Nascimento, A. C. (GFIC 2019: Proceedings of the 2nd Global Forum of Intellectual Capital, 2019)
The lifeworlds of large parts of the human population have undergone profound transformations through the expansion of the internet. Yet great parts of the world are still totally or partially offline. Cheap smartphones, tablets and (off-grid) electricity reach ever more of these populations. Scientists’ fascination with the internet – where money, investments, business models, communication, political control, as well as their lifeworlds converge - has largely obscured the potential of offline digitised information for the storage and distribution of information and the appropriation of knowledge. The profound changes of the socialisation of human knowledge through the revolutions in the transmission media have influenced how societies produce, distribute, receive and appropriate information. The expansion of access to digitised information revolutionises horizontal and vertical transmission. The differences are manifold: physical requirements are reduced – a whole library fits into a pocket; digital information is much cheaper to acquire; logistic chains through which books or journals are produced, shipped, distributed and stored are as unnecessary as are libraries. The actual access to information is also vastly different – the electronic search function and the offline Wikipedia may serve as examples. This suggests a rethinking of the “digital divide” which is no longer synonymous with internet access. Is there rather a frontier zone where different forms of access overlap? What are the distribution and market mechanisms for offline digital information? To what uses can digitised information be put offline? How will the new availability of ever cheaper technology affect knowledge production and appropriation?